1979
DOI: 10.1302/0301-620x.61b2.438274
|View full text |Cite
|
Sign up to set email alerts
|

School screening for scoliosis in Athens

Abstract: A randomly selected sample of 3494 children evenly representing a total population of 37 391 schoolchildren aged between eleven and twelve was screened for idiopathic scoliosis by the bending test. Ten per cent of the children showed clinical evidence of scoliosis and 6.4 per cent had positive radiological findings. Small curves were equally distributed between the two sexes, while large ones were more common in girls. Children with fair hair and blue eyes showed a higher percentage of positive findings than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 1 publication
1
15
0
8
Order By: Relevance
“…Diversos autores relatam uma maior prevalência no sexo feminino, concordando com nossos estudos, onde observamos uma alta prevalência no sexo feminino 18,19 . Wajchenber et al 7 apresentaram que a frequência de escoliose idiopática na população é de 0,5% a 10%, sendo a que a relação em sua amostra foi de 96 mulheres e quatro homens.…”
Section: Discussionunclassified
“…Diversos autores relatam uma maior prevalência no sexo feminino, concordando com nossos estudos, onde observamos uma alta prevalência no sexo feminino 18,19 . Wajchenber et al 7 apresentaram que a frequência de escoliose idiopática na população é de 0,5% a 10%, sendo a que a relação em sua amostra foi de 96 mulheres e quatro homens.…”
Section: Discussionunclassified
“…13 Similarly, a Greek study showed 10% prevalence of scoliosis and higher percentage of scoliosis was noted in fair haired blue eyed children as compared with dark complexioned children. 19 In Singapore, there was a signiÞ cantly higher prevalence of AIS in Chinese girls as compared with Malay and Indian girls. 36 AIS is predominantly common among girls and its incidence increases with higher age group.…”
Section: N Umber Of Cases Agementioning
confidence: 99%
“…The school screening program for the early detection of spinal deformities was introduced and reported in nineteen seventies 7,10,13,[16][17][18][19]23,37,39,46 and is now being practiced in different contries.…”
Section: Figure 1 Anatomical Distribution Of Curvementioning
confidence: 99%
See 1 more Smart Citation
“…SSS has been established as a valuable method for early detection of the disease and prophylaxis for severe deformity [9,10] . SSS has been practiced widely in the United States (US) and throughout the world for nearly 60 years [4] .…”
Section: Introductionmentioning
confidence: 99%